2021
DOI: 10.1186/s12870-021-03330-w
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and population structure analysis in a large collection of Vicia amoena in China with newly developed SSR markers

Abstract: Vicia amoena is a high-nutritional quality forage similar to alfalfa. However, studies on the genetic background of V. amoena are scarce. In the present study, the genetic variation of 24 V. amoena populations was assessed with newly developed simple sequence repeat (SSR) markers. A total of 8799 SSRs were identified in the V. amoena genomic-enriched sequences, and the most abundant repeat number was four. A total of 569 sampled individuals were assayed to evaluate the genetic diversity of the V. amoena popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 46 publications
1
7
0
Order By: Relevance
“…Excluding mononucleotide repeats, trinucleotides were found to be the most abundant repeats in the present study. This result was consistent with previous studies in other plants, such as Curcuma alismatifolia [ 42 ], Vicia amoena [ 22 ], and Pseudotaxus chienii [ 55 ]. Importantly, the abundance of trinucleotides in coding regions does not change the coding frame and therefore may not affect the functions of the genes [ 56 , 57 ].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Excluding mononucleotide repeats, trinucleotides were found to be the most abundant repeats in the present study. This result was consistent with previous studies in other plants, such as Curcuma alismatifolia [ 42 ], Vicia amoena [ 22 ], and Pseudotaxus chienii [ 55 ]. Importantly, the abundance of trinucleotides in coding regions does not change the coding frame and therefore may not affect the functions of the genes [ 56 , 57 ].…”
Section: Discussionsupporting
confidence: 93%
“…It has the advantages of good reproducibility, codominance, abundant polymorphisms, and easy detection [ 20 ]. In recent years, SSR markers have been widely used in genetic diversity analysis [ 21 , 22 ], linkage genetic map construction and QTL identification [ 23 , 24 ], and marker-assisted breeding [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Traditional SSR development method is a di cult, costly and labour intensively process, but the next-generation sequencing technology can effectively identify a large number of SSRs at a small cost and effort compared to traditional methods. Its main advantage is the ability to generate a large amount of sequence data, from which a large number of whole genome and gene-based SSR loci can be isolated and developed [39,45]. As NGS techniques have become more advanced, different new methods of SSR marker development have been reported that can be grouped into genomic SSRs (gSSRs) distributed throughout the entire whole genome sequence and expression sequence tags SSRs (EST ssr) embedded in transcriptional sequences [46,47].…”
Section: Discussionmentioning
confidence: 99%
“…gov/ sra/ PRJNA 698794). SSR marker detection, identification and primer design were performed as described by [31].…”
Section: Rna Sequencing and Core Ssr Marker Screeningmentioning
confidence: 99%
“…The three clusters formed in the dendrogram revealed that the geographic origin does not exactly corroborate genetic diversity. This phenomenon appeared in many SSR marker-based genetic diversities, such as Sesamum indicum [2,20], Camellia oleifera [4], Vicia amoena [31] and Trifolium repens [32]. Wu et al carried out genetic diversity analysis of Trifolium repens using PCoA, UPGMA and STRU CTU RE, and indicated that UPGMA analysis was implemented based on genetic distance, which provided more detailed relationships [32].…”
Section: Genetic Diversity and Relatednessmentioning
confidence: 99%